Triphenylphosphine Mediated Synthesis of Functionalized Benzo-Fused Coumarins from Some OH Acids and Dialkyl Acetylene Dicarboxylate. (19th August 2013) - Mohtat, Bita; Nahavandian, Semiramis; Razaghi, Maryam; Farsijani, Saeedeh; Djahaniani, Hoorieh
Abstract : Benzo-fused coumarins are prepared from 4-quinolinol by treatment with PPh3 and dialkyl acetylenedicarboxylate. Angular coumarins are prepared from 3-isoquinolinol and 7-hydroxyl coumarine with PPh3 and dialkyl acetylenedicarboxylate.